Draft Five Year Plan 1978 -83 Urban Development Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
A statutory board has been established under the Water Prevention & Control of Pollution Act, 1974 In Madhya Pradesh. This Board was set up in September, 1974. The preamble of the Act states, "The maintaining and restoring of wholesomeness of water..............". The Board has large number of functions, but broadly it has to regulate the industrial pollution and domestic pollution by proper granting of consent for discharges into natural waters by the polluters and plan comprehensive programme in the state for economical, scientific methods by which the harmful effluents are treated.
Government of Madhya Pradesh, Planning, Economics and Statistics Department